KELAYAKAN KAMUS MINI ISTILAH TEKS EKSPLANASI SEBAGAI REFERENSI BELAJAR DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS Xl SMAS BINA BERSAUDARA MEDAN - Nurhabilla Nurhabilla; Rika Kartika; Ratna Soraya (UNIVERSITAS DHARMAWANGSA, 2025)
This study aimed to develop a mini dictionary of explanatory text terms as a learning reference material in learning Indonesian language for students of class XI SMAS Bina Saudara Medan. The population of this study were students of class XI IPA and XI IPS totally 55 students. The sample was students of class XI IPA totally 30 students. The research instrument used was a questionnaire with data collection techniques in the form of observation, interviews and questionnaires. This study used Research and Development (R&D) using the Borg and Gall learning model with 10 stages, namely research and data collection, planning, developing initial products, field trials, product revisions, field testers, and final product revisions. The results of this study indicated that the mini dictionary of terms in class XI IPA SMAS Bina Bersuara Medan that gets a feasible category with a percentage as 84.53%. Based on the results of the assessment of material experts I, the criteria for